Model of Political Movements of the Public Sector in Bangkok, Thailand - Kanchanawongpaisan, Sipnarong; Srison, Wijittra (Suan Dusit Graduate School Academic Journal, 2025)
The research “Model of Political Movements of the Public Sector in Bangkok, Thailand” had the following objectives: 1) To study the level of factors related to social media usage behavior, social movements, and political motivations influencing political movements; 2) To examine the causal relationship patterns of social media usage behavior among the civil society in Bangkok; and 3) To develop a model for political movements of civil society in Bangkok. The study employed a mixed methods research design, collecting quantitative data from the sample of 300 participants in the northern areas of Bangkok selected by using stratified random sampling to analyze variable relationships. Instrument reliability was tested using Cronbach's alpha, yielding a value of .895, and content validity was confirmed with an IOC score of .67. The statistical significance level of .05 was set for the analyses. Qualitative data were collected through in-depth interviews with key informants, such as activists, community leaders, and the general public. The research findings revealed that 1) The factors of social media usage behavior, social movements, political motivations, and the patterns of political movements of civil society were found at the high level; 2) The structural equation model test indicated that the model was consistent with the empirical data; and 3) The model of political movements was derived from internal factors, which included media awareness that led to behavior and political motivations, influencing external outcomes such as social movements and, ultimately, political movements. This phenomenon enabled individuals to participate in political activities effectively and conveniently due to online communication, making it difficult for government authorities to prevent gatherings.